The Correlation of Writing Competency Using Indonesian Sentence Structure and Achievement Motivation on Class Student Learning Outcomes XII - Hasibuan, Maya Syahfitri; Sutikno (PT Inovasi Pratama Internasional, 2024)
The problem in this research is the correlation between writing competence using Indonesian sentence structures and achievement motivation on the learning outcomes of class XII students at MA Al-Hidayah Teluk Panji, Kampung Rakyat District for the 2023-2024 academic year. This research aims to determine the correlation between writing competence using Indonesian sentence structures and achievement motivation together on the learning outcomes of class XII students at MA Al-Hidayah Teluk Panji, Kampung Rakyat District for the 2023-2024 academic year. The method used in this research is a descriptive method with correlation analysis techniques. The population in this study was all class The instruments used in data collection were tests and questionnaires. Tests are used to obtain data about the ability to use sentence structure and write exposition, and questionnaires are used to obtain data about students' achievement motivation. The results of the research show that there is a relationship between the ability to use sentence structure and achievement motivation together on the learning outcomes of class XII students at MA Al-Hidayah Teluk Panji at a significance level of 5%. Compared with the assessment criteria that have been proposed previously, it turns out that the tcount test value is greater than the ttable, so the Ha hypothesis is accepted. Thus, the ability to use sentence structure also has a relationship in writing expositions and student achievement motivation has a relationship in writing expositions in class XII students at MA Al-Hidayah Teluk Panji, Kampung Rakyat District, the academic year 2023-2024.